2018
DOI: 10.29252/jafm.11.01.28080
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Convection Heat Transfer of Al2O3 Nanofluid on the Elliptical Shapes: Numerical Study of Irreversibility

Abstract: In this study the 2D laminar and steady water-based Al2O3 nanofluid flow over a cylinder with circular, horizontal and vertical elliptical cross section by constant surface temperature boundary condition has been studied. The main goal of this research is to investigate the effects of different natural and mixed convection heat transfer mechanisms on the convective heat transfer coefficient, and the entropy generation due to the thermal and frictional origination. Conservation equations of the mass, momentum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The study revealed that the local heat transfer coefficient is a direct function of Ra . Khajeh et al 13 considered lid‐driven convective heat transfer of Al 2 O 3 on elliptical configurations with entropy generation incorporated. They showed that in the presence of irreversibility, heat transfer augmentation was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed that the local heat transfer coefficient is a direct function of Ra . Khajeh et al 13 considered lid‐driven convective heat transfer of Al 2 O 3 on elliptical configurations with entropy generation incorporated. They showed that in the presence of irreversibility, heat transfer augmentation was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Khajeh et al. (2018), [ 42 ] presented laminar Al 2 O 3 nanofluid flow over cylinder with different cross section, the results focused on convective heat transfer coefficient and the entropy generation. Entropy generated and nanoparticles volume fraction enhanced heat transfer according to the results.…”
Section: Introductionmentioning
confidence: 99%